2007
DOI: 10.1194/jlr.m600545-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E•dipalmitoylphosphatidylcholine particles are ellipsoidal in solution

Abstract: Apolipoprotein E (apoE) is a major protein component of cholesterol-transporting lipoprotein particles in the central nervous system and in plasma. Polymorphisms of apoE are associated with cardiovascular disease and with a predisposition to Alzheimer's disease and other forms of neurodegeneration. For full biological activity, apoE must be bound to a lipoprotein particle. Complexes of apoE and phospholipid mimic many of these activities. In contrast to a widely accepted discoidal model of apoA-I bound to dimy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
73
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(81 citation statements)
references
References 43 publications
7
73
1
Order By: Relevance
“…Lipidation of apoE and its domains has only a small effect on the affinity for apoC-II fibrils, suggesting that there is limited structural change in apoE at the sites of interaction. This is consistent with models of lipoprotein-bound apoE, which suggest that helix three is curved around the lipoprotein surface, with the hydrophobic face interacting with the lipid surface (54,55). This conformation would still allow basic residues on helix three of apoE to interact with alignments of negative charges on amyloid fibrils as shown in Fig.…”
Section: Discussionsupporting
confidence: 74%
“…Lipidation of apoE and its domains has only a small effect on the affinity for apoC-II fibrils, suggesting that there is limited structural change in apoE at the sites of interaction. This is consistent with models of lipoprotein-bound apoE, which suggest that helix three is curved around the lipoprotein surface, with the hydrophobic face interacting with the lipid surface (54,55). This conformation would still allow basic residues on helix three of apoE to interact with alignments of negative charges on amyloid fibrils as shown in Fig.…”
Section: Discussionsupporting
confidence: 74%
“…From this work, it was shown that the E422k fold was consistent with a helical hairpin (Fig. 1B), providing experimental evidence of the existence of the hairpin structures computationally modeled in this study (54,55). Although our initial modeling efforts have focused on the double-belt model, there is much conjecture on the nature of the lipid-protein interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Small amounts of CE have previously been reported in fi broblast-and macrophage-derived nHDL ( 45 ). Because cholesteryl esters are much more hydrophobic than cholesterol, it is very likely sequestered in the core of nHDL particle and may constitute the beginnings of a hydrophobic core that yields spheroidal particles ( 71 ). Previous biophysical studies have demonstrated that CE was soluble in phospholipid up to about 3 mol%, whereas above that concentration there was phase separation ( 72 ).…”
Section: Discussion Nhdl Lipidsmentioning
confidence: 99%